2022
DOI: 10.1177/08853282221133647
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosome yield characteristics modeling of acidithiobacillus ferrooxidans in airlift bioreactor using response surface methodology

Abstract: Bacterial magnetosomes had been proved to have great application potential in medicine and biotechnology. The objective of the present study was to obtain high yield of magnetosomes from Acidithiobacillus ferrooxidans ( A. ferrooxidans) BYM in an airlift bioreactor using response surface methodology (RSM). The magnetosomes from A. ferrooxidans BYM were characterized using a transmission electron microscope and scanning electron microscopy. The maximum magnetosome yield of 0.4267 mg/L was achieved at ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…In the past, it has been demonstrated that even some non-magnetotactic bacteria, including Magnetospirillum aberrantis, A. ferrooxidans, and Leptospirillum ferriphilum, can perceive a magnetic field and produce magnetosomes [65,99]. It is also known that A. ferrooxidans does not exhibit magnetotaxis in the presence of the Earth's magnetic field, while weak magnetotaxis can be observed in an artificially induced magnetic field [65].…”
Section: Metal Recoverymentioning
confidence: 99%
“…In the past, it has been demonstrated that even some non-magnetotactic bacteria, including Magnetospirillum aberrantis, A. ferrooxidans, and Leptospirillum ferriphilum, can perceive a magnetic field and produce magnetosomes [65,99]. It is also known that A. ferrooxidans does not exhibit magnetotaxis in the presence of the Earth's magnetic field, while weak magnetotaxis can be observed in an artificially induced magnetic field [65].…”
Section: Metal Recoverymentioning
confidence: 99%
“…The mass cultivation of A. ferrooxidans has been easily available with enough Fe(II) ( 9 ). Thus, A. ferrooxidans is conferring greater flexibility and potential application in biomagnetic nanoparticle production ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, current researches on Fe 3 O 4 nanoparticle synthesis in Acidithiobacillia spp. were only at the cellular level, but the topic on its molecular mechanism remains understudied ( 11 ). It is necessary to find potential key genes by multi-omic analysis and verify these genes by establishing genetic operation system, such as gene overexpression and knockout.…”
Section: Introductionmentioning
confidence: 99%